2022
DOI: 10.1155/2022/4088187
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Bacterial Isolates from the Urine Specimens of Urinary Tract Infected Patient

Abstract: Urinary tract infections (UTIs) maintained a serious public health concern, as did the growth in antibiotic resistance both between uropathogenic microorganisms. A regular assessment of the microbiological agents that cause UTIs, as well as their antimicrobial resistance, is essential for a tailored empirical antibiotic response. Knowing the variables that cause UTIs can help you intervene quickly and simply to get the condition under control. The most common infecting species in acute infection is Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This finding coincide with a study done in Rawalpindi, which reported a Gram-negative prevalence of 94% and a Grampositive prevalence of 6% [7]. Similarly, another study conducted in India found that 95% of the total isolates were Gram-negative [17]. In contrast, a study conducted in Italy reported a lower percentage of Gram-negative bacteria at 78.5% [10].…”
Section: Discussionsupporting
confidence: 86%
“…This finding coincide with a study done in Rawalpindi, which reported a Gram-negative prevalence of 94% and a Grampositive prevalence of 6% [7]. Similarly, another study conducted in India found that 95% of the total isolates were Gram-negative [17]. In contrast, a study conducted in Italy reported a lower percentage of Gram-negative bacteria at 78.5% [10].…”
Section: Discussionsupporting
confidence: 86%
“…The short distance between the urethra and the opening of the anus and bladder increases the possibility of infection caused by ascending uropathogens [12]. In general, about half of women experience a UTI in their late 20s [22]. Moreover, approximately 20-30% of women with a rst UTI will experience two or more infections.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of organisms identified as demonstrating MDR is increasing globally and in Iraq [7,8]. To reduce the mortality rate and morbidity arising from UTIs, such as renal abscesses, sepsis, and subsequent renal impairment from fibrosis, it is essential to swiftly recognize the presence of UTIs and institute antibiotic treatment [9]. An acute UTI is typically managed according to the patient's symptomatology and urinalysis without confirmation from microbiological investigations [10,11].…”
Section: Introductionmentioning
confidence: 99%